The altered landscape in urban low cost terrace housing: an expression of the cultural landscape authenticy - Ismail, Nor Atiah; Ismail, Sumarni; Ariffin, Noor Fazamimah (Science Publishing Corporation, 2019)
Provision of adequate housing was the major concern of Malaysian housing policy before independence and it is still, continue to be an important development entities. This paper discusses on the findings of a research that investigates and interprets the alteration to the landscape made by the urban low -cost housing residents. The study adopted a post -occupancy evaluation method (POE), a research aproach that aimed at understanding the end -users satisfaction with regard to the provided living environment. The research involving residents with low socio -economic backgrounds. Research finding informs that the altered landscape created by community can be considered as a genuine expression of their cultural landscape authenticity and way of life. This findings may help relevant Malaysia government agencies and industry players to better understand the community everyday landscape issues and the community needs for each of these housing schemes, rather than providing the current ‘one design fits all’ in a low -cost terrace housing.